IMPLEMENTASI DIGITAL MARKETING UNTUK MENINGKATKAN PENJUALAN PAKET UMROH : (STUDI KASUS PT. TRIDAYA PESONA WISATA CABANG BUKITTINGGI) - M. Alfin Pauzi Harahap; Jon Kenedi (ADISAM PUBLISHER, 2024)
This research aims to determine the implementation of digital marketing at PT. Tridaya Pesona Wisata Bukittinggi Branch and find out the impact of implementing digital marketing to increase sales of Umrah packages at PT. Tridaya Pesona Wisata Bukittinggi Branch. This type of research is field research, which takes data directly from the research site. Based on the results of the research conducted, it is clear that the digital marketing carried out by PT Tridaya Pesona Wisata Bukittinggi branch is in line with Yazer Nasdini's theory which states that there are indicators in the implementation of digital marketing, namely accessibility, interactivity, entertainment, trust, irritation and informativeness. The digital marketing instruments used by PT Tridaya Pesona Wisata include websites and social media marketing such as: Facebook and Instagram. As well as the positive and effective impact of implementing PT Tridaya Pesona Wisata's digital marketing which helps provide accurate and detailed information to prospective pilgrims as well as increasing sales of Umrah packages and the number of pilgrims using Umrah travel services with PT. Tridaya Pesona Wisata Bukittinggi Branch.